Pneumococcal vaccination at 65 years and vaccination coverage in at-risk adults: A retrospective population-based study in France - Wyplosz, Benjamin; Grenier, Benjamin; Roche, Nicolas; Roubille, François; Loubet, Paul; Sultan, Ariane; Fougère, Bertrand; Fernandes, Jérôme; Duhot, Didier; Moulin, Bruno; Raguideau, Fanny; Blanc, Emmanuelle; et al. (PloS one, 2025)
Age (> 50 years) is a risk factor for pneumococcal disease, but is not an indication for vaccination in France, by contrast to influenza. In 2018, the pneumococcal vaccine coverage rate (VCR) was 4.5% in adults at-risk, in contrast to the influenza VCR, which was 43.6%. We aimed to assess pneumococcal and influenza VCR in 2020 in the entire French population and factors associated with a higher VCR (including the age of 65 years). We retrospectively included all adults covered by the National Health Service in 2020 and identified patients at-risk using validated algorithms. We assessed VCRs by analysing pneumococcal vaccines reimbursed between 2009 and 2020 (13-valent pneumococcal conjugate vaccine [PCV13] and 23-valent polysaccharide vaccine [PPSV23]), and influenza vaccines reimbursed between September 2020 and March 2021. In 2020, we identified 7,336,769 adults at risk (median age: 67.0 years): 84.2% had comorbidities and 24.5% were immunocompromised. The overall pneumococcal VCR (PCV13 + PPSV23) was 9.9% and the seasonal influenza VCR was 51.1%. The variable associated with the highest odds of VCR was an "age ≥65 years" for influenza (odds ratio [OR] 4.14), but not for pneumococcal vaccination (OR 1.02). In patients with comorbidities, pneumococcal VCR did not significantly increase between those aged 18-65 years and those aged > 65 years (7.2% to 9.4%), and even decreased from 20% to 17.9% in patients with immunodeficiencies. In contrast, influenza VCR increased significantly from 35.5% to 67.9% (OR 3.55) in patients with comorbidities, and from 27.3% to 71.2% (OR 5.57) in those with immunodeficiencies. In France, pneumococcal VCR did not increase above 65 years of age (OR 1.02), by contrast to influenza VCR (OR 4.14) that increased significantly, suggesting that an age-based recommendation for pneumococcal vaccination will probably benefit to VCR in at-risk, elderly population.